Pengaruh Indikator Perilaku Hidup Bersih dan Sehat (PHBS) Terhadap Gejala Pneumonia Pada Balita di Puskesmas Mojopanggung (perkotaan), Puskesmas Tapanrejo (pedesaan) dan Puskesmas Kedungrejo (pesisir) Banyuwangi - Dyah Ayu; Sugeng Winarso; Dewi Rokhmah (Multidisciplinary Journal, 2020)
HCLB Program for the households is an attempt to provide knowledge for the family members to practice clean, health living behavior and to participate in the health of community environment. HCLB purpose is the health of the family members. The health level of individuals, family, community and environment is related HCLB. In the household level, there are 10 HCLB indicators to be practiced by the family members. HCLB should be started from the household since its health, considered as the asset of development, should be taken care of. This research aims to analyze the effect of HCLB program on pneumonia symptom in toddlers in Mojopanggung Community Health Centre (citiy), Tapanrejo Community Health Centre (village), Kedungrejo Community Health Centre (coastal area) of Banyuwangi. This research applies analytic descriptive using case control approach and ordinal regression data analysis with the population of 8,883 respondents. The sample includes simple random sampling of 104 respondents. The findings shows that there is an effect of HCLB Program on Penumonia symptoms on toddlers with significant value of 0,001 in Mojopanggung Community Health Centre, of 0,0026 in Tapanrejo Community Health Centre and of 0,0029.in Kedungrejo Community health centre. Keywords: Healthy and Clean Living Behaviour (HCLB), Pneumonia, Toddlers